IMPROVING THE METHODS OF ASSESSING THE COMPETITIVENESS OF LIGHT INDUSTRY ENTERPRISES - Mirzaabdullayeva Gulnora (International Engineering Journal For Research & Development, 2020)
The issue of assessing the competitiveness of economic entities and the development of scientific and methodological bases for the formation of strategies for the development of their market activities is a very important issue. This paper proposes a method of assessing the competitiveness of light industry enterprises based on operational efficiency, innovation activity and market share, and recommendations on its methodological basis are prepared and based on practicality.